Exploring the role of correlations for analyzing the Malaysia road accident problem - Mohd. Rijal, Omar; Chang, Yun Fah; Mohd. Noor, Norliza (Universiti Teknologi Malaysia, 2002)
The belief or misconception that correlation may mean causation has seen widespread use of various types of correlations in the analysis of numerical data. The role of correlation, in particular partial correlations, in specific areas of data analysis; approach of problem, interrelationships of variables and modeling will be considered in a particular case study, namely the Malaysian road accident problem